2020
DOI: 10.1101/2020.05.26.115923
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

T-cell hyperactivation and paralysis in severe COVID-19 infection revealed by single-cell analysis

Abstract: Severe COVID-19 patients can show respiratory failure, T-cell reduction, and cytokine release syndrome (CRS), which can be fatal in both young and aged patients and is a major concern of the pandemic. However, the pathogenetic mechanisms of CRS in COVID-19 are poorly understood. Here we show single cell-level mechanisms for T-cell dysregulation in severe SARS-CoV-2 infection, and thereby demonstrate the mechanisms underlying T-cell hyperactivation and paralysis in severe COVID-19 patients. By in silico sorting… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…In summary, Gal-3 is a lectin that exhibits a pleiotropic role in mediating the acute and chronic consequences of infection and inflammation. Multiple studies have shown Gal-3 to be highly upregulated in patients suffering from severe COVID-19 ( De Biasi et al, 2020 ; Kalfaoglu et al, 2020 ; Liu et al, 2020 ). On a cellular level, Gal-3 is most highly expressed in monocytes, macrophages, and dendritic cells during severe COVID-19 infection ( Liu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, Gal-3 is a lectin that exhibits a pleiotropic role in mediating the acute and chronic consequences of infection and inflammation. Multiple studies have shown Gal-3 to be highly upregulated in patients suffering from severe COVID-19 ( De Biasi et al, 2020 ; Kalfaoglu et al, 2020 ; Liu et al, 2020 ). On a cellular level, Gal-3 is most highly expressed in monocytes, macrophages, and dendritic cells during severe COVID-19 infection ( Liu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, significantly elevated levels of Gal-3 have been shown in the serum of patients suffering from severe COVID-19 as compared to those with mild disease ( De Biasi et al, 2020 ). On a cellular level, Gal-3 was shown to be most elevated in immune cells during severe COVID-19 ( Kalfaoglu et al, 2020 ) The highest levels of Gal-3 were seen in infected macrophages, monocytes, and dendritic cells, the very cells responsible for initiating CSS ( Liu et al, 2020 ). A pathway through which Gal-3 may contribute to the development of CSS is detailed in Figure 2 .…”
Section: Gal-3 In Severe Infection: Promoting Immunologic Sequelae Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed investigation of Tregs in the lung tissues of severe COVID-19 patients and their molecular signatures would provide insight on these questions. However, in silico analyses performed on the transcriptomic data of CD4 + T-cells from the COVID-19 patient's bronchoalveolar lavage suggest that IL2 transcripts were reduced in severe cases compared with mild cases [10]. Therefore, reduced IL2 would lead to enhanced apoptosis of Tregs and is also confirmed by reduced levels of FoxP3.…”
mentioning
confidence: 98%
“…The most common reported comorbidities associated with poor outcomes in include hypertension, diabetes, cardiovascular disease, and chronic respiratory infections [4,5]. However, the underlying molecular mechanisms in severe COVID-19 and their interplay with such comorbidities or clinical factors are poorly understood [6].…”
Section: Introductionmentioning
confidence: 99%